Japan and the Third World : - Nester, William Raymond (Macmillan academic an professional ltd, 1992)
Since 1945, Japan's policymarkets have viewed geoeconomic rather than geopolitical influence as the most important source of power in an increasingly interdependent world political economy. Japanese policy toward the Third World is a vital part of its neomercantilist drive to transform Japan's comprehensive security...